In Vitro and In Vivo Antitumor Activities of Tenacissoside C from Marsdenia tenacissima - Ye, Bengui; Yang, Jinrong; Li, Jun; Niu, Ting; Wang, Shu (Planta Medica, 2014)
Tenacissoside C, a natural bioactive compound of C21 steroidal saponins, was isolated and purified from air-dried stems of Marsdenia tenacissima. In the present study, the MTT assay showed that tenacissoside C exhibited obvious cytotoxicity in K562 cells with IC50 values of 31.4, 22.2, and 15.1 µM for 24, 48, and 72 h, respectively. Flow cytometry analysis indicated that the antiproliferative activity induced by tenacissoside C might be executed via G0/G1 cell cycle arrest and proapoptosis in K562 cells. Western blotting analysis elucidated that: A) Tenacissoside C induced K562 cell cycle (G0/G1) arrest via downregulating cycline D1 protein expression; and B) Tenacissoside C induced K562 cell apoptosis via the mitochondrial pathway by downregulating Bcl-2 and Bcl-xL protein expression, upregulating Bax and Bak protein expression, and activating caspase-9 and caspase-3. In vivo, significant tumor growth inhibition activity of tenacissoside C was observed in K562 cell-bearing nude mice, accompanied by a significant antiangiogenic effect in vivo against K562 cells (a marked decrease in MVD) and associated with enhanced apoptotic cell death (TUNEL staining assay in vivo), both in dose-dependent manners. The treatment with tenacissoside C did not significantly affect body mass and macroscopic examination of the organs in this mouse tumor model.
Keywords: Marsdenia tenacissima; Asclepiadaceae; tenacissoside C; antitumor; cytotoxicity; K562 cell; apoptosis